Pengetahuan Dan Sikap Ibu Dalam Menjaga Kebersihan Mulut Pada Bayi - Koekoeh Hardjito; R.E Wijayanti; Siti Fatkhur Rahmah (coba, 2014)
Oral thrush often found in babies and young children who drink milk with bottle/pacifiers and children taking fopspeen is not clean. The exixtences of residual milk can also be the cause of these sariawan. One effort to prevent sariawan is to maintain mouth hygiene of children. The purpose of this study was to identify the correlation between knowledge of mother about sariawan with attitude of mother to do oral hygiene for a baby. Method is used in this research is study analyze correlation with used approximaly cross sectional. Population of this research is all mother which is had baby Sample in this research is 33 person From statistic test with standart errors 5% (0.05) was gotten p= 0,020 < 0.05, so otherwise there is the correlation between knowledge of mother about sariawan with attitude of mother to do oral hygiene for a baby. Suggested to health staff for care increase service quality about health baby, So the mother can guard or correct the attitudes and behaviors in the care of her baby. Keyword : Knowledge, Attitude, Oral thrush, Oral Hygiene